Social Media and the Risk of Sexual Abuse Against Teens - Zatalini, Adhalia (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This study examines how social media risks such as anonymity and wide accessibility contribute to the vulnerability of teenagers to sexual harassment. The increasing use of social media among teenagers brings both positive and negative impacts. One of the serious risks that has emerged is sexual harassment, which can occur in various forms such as grooming, non-consensual sexting, cyberstalking, and revenge porn. Statistical data and case studies show a significant increase in incidents of sexual harassment on digital platforms. The psychological and social impacts of this harassment are highly detrimental, including depression, anxiety, trauma, social isolation, and a decline in academic performance. To address this issue, collaborative efforts are needed from parents, schools, and social media platforms in the form of education, supervision, and strict security policies. By increasing awareness and preventive actions, we can protect teenagers from the threat of sexual harassment on social media, making it a safer and more positive environment for their development.